Robots, Love, and Sex: The Ethics of Building a Love Machine - Sullins, J. P. (IEEE transactions on affective computing, 2012)
This paper will explore the ethical impacts of the use of affective computing by engineers and roboticists who program their machines to mimic and manipulate human emotions in order to evoke loving or amorous reactions from their human users. We will see that it does seem plausible that some people might buy a love machine if it were created, but it is argued here that principles from machine ethics have a role to play in the design of these machines. This is best achieved by applying what is known about the philosophy of love, the ethics of loving relationships, and the philosophical value of the erotic in the early design stage of building robust artificial companions. The paper concludes by proposing certain ethical limits on the manipulation of human psychology when it comes to building sex robots and in the simulation of love in such machines. In addition, the paper argues that the attainment of erotic wisdom is an ethically sound goal and that it provides more to loving relationships than only satisfying physical desire. This fact may limit the possibility of creating a machine that can fulfill all that one should want out of erotic love unless a machine can be built that would help its user attain this kind of love.